Marketing Communication Strategy on Instagram of Asa Cerra's Probiotic Drink - Maulana, Evinka Aisha; Wulansari, Amilia (Integrasi Sains Media, 2024)
The growth of Indonesia's probiotic, health, and wellness industry has compelled companies in this sector to adopt effective marketing communication strategies to address customer needs and preferences. Companies are increasingly promoting the value of their products by highlighting their benefits and ingredients. Asa Cerra, a new company preparing to launch its probiotic product